Retail Electricity Market Liberalization: An Overview of International Experience and Effects on the Chilean Regulated Tariff - Zolezzi-Cid, J; Becker-Cares, C; Verdejo-Fredes, H; Garcia-Munoz, F (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The Chilean government is looking to liberalize the retail electricity market to increase competitiveness and reduce the price of electricity for residential and small/medium commercial customers. Under this context, the article aims to enrich the legislative debate by providing an overview of the international experience of the electricity market liberalization that started in the early 1990s and presents forecasting for the regulated Chilean price until 2034, considering the current tenders and the price stabilization mechanism. In addition, multiple simulations are developed to measure the market effect of retail liberalization on regulated customers. In this regard, the results suggest a significant regulated price increase from 2022 to 2032, produced mainly by the stabilization mechanism, which overshadows the low prices obtained in recent renewable generation supply tenders. However, if the retail market is liberalized, the simulation indicates that regulated customers could save between 15% and 20% on their electricity bills. © 2022 by the authors.